(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
I am in this article on light and temperature sensors in devices of alternative energy sources. Advantages of using sensors in alternative energy devices. Problems in the introduction of sensors in alternative energy devices. Application of temperature sensors in alternative energy devices. Like the application of light sensors in alternative energy devices . I covered the data.